2002
DOI: 10.1007/s00424-002-0806-0
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic tryptophan hydroxylase and the hypothalamic-pituitary-adrenocortical response to water deprivation and hydration in vasopressin-deficient and normal rats

Abstract: The effects of water deprivation and hydration on plasma corticosterone concentration and the activity of tryptophan hydroxylase (TPH), the rate-limiting enzyme in serotonin (5-HT) biosynthesis, in the hypothalamus of vasopressin- (AVP-) deficient homozygous Brattleboro and normal Wistar rats were studied. In the Wistar rats, water deprivation caused an increase in the TPH activity in the anterior and middle (infundibular) parts of the hypothalamus, while hydration did not affect the activity of the enzyme in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
2
4
0
1
Order By: Relevance
“…These results suggest that nNOS gene expression in the PVN neurons may be regulated depending on the osmotic condition of the body. Interestingly, the plasma corticosterone level changed in parallel with the PVN nNOS expression under different water conditions; i.e., it was increased by water deprivation, in accordance with previous reports (Kiss et al, 1994;Watts, 2000;Popova et al, 2002), and partially recovered by 1 hr of rehydration. However, the nNOS gene does not carry a glucocorticoid response element in its upstream promoter region (Jeong et al, 2000).…”
Section: Discussion Nnos Expression In the Pvn And Plasma Corticosteronesupporting
confidence: 89%
“…These results suggest that nNOS gene expression in the PVN neurons may be regulated depending on the osmotic condition of the body. Interestingly, the plasma corticosterone level changed in parallel with the PVN nNOS expression under different water conditions; i.e., it was increased by water deprivation, in accordance with previous reports (Kiss et al, 1994;Watts, 2000;Popova et al, 2002), and partially recovered by 1 hr of rehydration. However, the nNOS gene does not carry a glucocorticoid response element in its upstream promoter region (Jeong et al, 2000).…”
Section: Discussion Nnos Expression In the Pvn And Plasma Corticosteronesupporting
confidence: 89%
“…Our current results support our previous results by demonstrating that serotonin and AVP can interact to regulate the renal response to a natural osmotic challenge [32]. They also extend them by showing that serotonin is able to prevent the activity of the AVP system in the area of the anterior hypothalamus from being depressed by impulses from osmoreceptors under natural water intake.…”
Section: Discussionsupporting
confidence: 81%
“…Our previous studies in Wistar and AVP-deficient Brattleboro rats have demonstrated the involvement of the serotonin brain system in the central mechanisms of water balance regulation [32]. These results suggested that not only may serotonin participate in the regulation of AVP secretion, but AVP may also modulate serotonin metabolism and the response of the serotonergic system to water deprivation.…”
Section: Introductionmentioning
confidence: 83%
“…that AVP is required for the HPA response to osmotic stimuli. Water deprivation in Brattleboro rats led to a similar conclusion (Popova et al 2002). It is possible that oxytocin compensates for the loss of AVP in this process as it is also stimulated by osmotic challenges (Schlosser et al 1994).…”
Section: Discussionmentioning
confidence: 81%